2020
DOI: 10.3389/fpls.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Aldoxime Metabolism Is Linked to Phenylpropanoid Production in Camelina sativa

Abstract: Plants produce diverse secondary metabolites. Although each metabolite is made through its respective biosynthetic pathway, plants coordinate multiple biosynthetic pathways simultaneously. One example is an interaction between glucosinolate and phenylpropanoid pathways in Arabidopsis thaliana. Glucosinolates are defense compounds made primarily from methionine and tryptophan, while phenylpropanoids are made from phenylalanine. Recent studies have shown that the accumulation of glucosinolate intermediate such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…We verified that all four KFBs that functioned redundantly in PAL degradation were upregulated in both ox‐1/WT and ox‐2/WT in a manner similar to IAOx‐based or aliphatic aldoxime‐based induction (Fig. 5e) (Kim et al, 2020; Zhang et al, 2020). This suggested that IAOx and PAOx shared all three of the known outcomes of aldoxime metabolism in Brassicales species: production of defence compounds, auxin biosynthesis and repression of the phenylpropanoid pathway (Fig.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…We verified that all four KFBs that functioned redundantly in PAL degradation were upregulated in both ox‐1/WT and ox‐2/WT in a manner similar to IAOx‐based or aliphatic aldoxime‐based induction (Fig. 5e) (Kim et al, 2020; Zhang et al, 2020). This suggested that IAOx and PAOx shared all three of the known outcomes of aldoxime metabolism in Brassicales species: production of defence compounds, auxin biosynthesis and repression of the phenylpropanoid pathway (Fig.…”
Section: Resultssupporting
confidence: 67%
“…The 35S:AtCYP79A2 and 35S:ZmCYP79A61 constructs were introduced into wild‐type (Col‐0), or ref2‐1 plants via Agrobacterium tumefaciens (GV3101)‐mediated transformation by following a method shown in Zhang et al . (2020). More than 10 T1 plants were screened by application of 0.2% Basta (Rely 280; BASF, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations